(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In article, the author investigates features of thought process, the law of development of cognitive activity, characterizes stages of informative search, proves a role of the teacher at creation of a problem situation and analyzes conditions of incision of pupils n problem search activity.